Validation of taxon names described in “Deltocephalinae from China (Hemiptera: Cicadellidae)” - Dmitriev, Dmitry A.; Li, Zizhong; Dai, Renhuai; Xing, Jichun (Zootaxa, 2024)
The purpose of this paper is to validate 4 generic names and 34 specific names previously introduced in the “Deltocephalinae from China (Hemiptera: Cicadellidae)” by Li, Dai & Xing (2011). The names are unavailable in the original publication, because of the missing information on the type specimen repository. The following genera and species are introduced as new in this publication: Bambusananus, Li & Xing; Branchana Li; Cyclevertex Li & Xing; Lineana Li & Xing; Abrus biprocessus Li; Abrus graciaedeagus Li; Bambusana biflaka Li; Bambusana nigrimaculata Li; Bambusananus furcatus Li & Xing; Branchana xanthota Li; Cyclevertex furcatum Li & Xing; Lineana albipunctata Li & Xing; Lineana ductaedeagusa Li & Xing; Protensus nigrifrons Li & Xing; Protensus yanheensis Li & Xing; Paramesodes menghaiensis Xing & Li; Yuanamia producta (Xing & Li, 2011); Hishimonoides brevis Li, 2011; Litura tripunctata Li; Changwhania huajiangensis Xing & Li; Elginus productus Xing & Li; Metalimnus maoershanensis Xing & Li; Nicolaus bihamatus Xing & Li; Paralaevicephalus bisubulatus Xing & Li; Paralaevicephalus brevissimus Xing & Li; Paralaevicephalus spinosus Xing & Li; Scaphoideus annulatus Li; Scaphoideus bannaensis Li; Longicornus longus Xing & Li; Melanetettix mengyangensis Xing & Li; Osbornellus aurantius Xing & Li; Osbornellus suiyangensis Xing & Li; Osbornellus conoideus Xing & Li; Phlogothamnus acutaedeagus Li; Phlogothamnus luteoguttatus Li; Phlogothamnus productus Li & Xing; Phlogothamnus rugosus Li; Phlogotettix fanjingshanensis Li.